Protection against tobacco mosaic virus in transgenic plants that express tobacco mosaic virus antisense RNA. - Powell, P A (1989)
Transgenic tobacco plants that express RNA sequences complementary to the tobacco mosaic virus (TMV) coat protein (CP) coding sequence with or without the tRNA-like structure at the 3' end of the TMV RNA were produced. Progeny of self-pollinated plants were challenged with TMV to determine their resistance to infection. Plants that expressed RNA sequences complementary to the CP coding region and the 3' untranslated region, including the tRNA-like sequences, were protected from infection by TMV at low levels of inoculum. However, plants that expressed RNA complementary to the CP coding sequence alone were not protected from infection. These results indicate that sequences complementary to the terminal 117 nucleotides of TMV, which include a putative replicase binding site, are responsible for the protection. However, the level of protection in these plants was considerably less than in transgenic plants that expressed the TMV CP gene and accumulated CP. Since the mechanisms of protection in the two systems are different, it may be possible to increase protection by introducing both sequences into transgenic plants.